Desempenho da palma forrageira em segundo ciclo sob irrigação complementar com esgoto doméstico tratado nas condições semiáridas - Azevedo Junior, Manoel Simões de (2017)
Due to the limited supply of water for agriculture in the northeastern semi-arid region, it is necessary to use more efficient and appropriate technologies for the use of water resources, such as the reuse of water for irrigation and the cultivation of plants that produce in situations of low water supply, forage palm In this context, it was verified the performance of elephant ear palm (Opuntia sp) under complementary irrigation with domestic sewage treated in its second cycle. The experiment was carried out in the settlement Miracle, Apodi / RN, from June / 2016 to February / 2017. Five treatments, four irrigation frequencies (2.3, 7, 14 and 21 days) were used to apply a 3.5 mm effluent blade, and the control, without irrigation. A randomized complete block design with four replicates was used. Domestic sewage water after primary-primary treatment presented acceptable chemical and biological characteristics for fertigation under the conditions used in palm cultivation. After 234 days of the palm cut, measurements were made of the morphometric characteristics: plant height, length, width, perimeter, thickness and number of primary and secondary cladodes. The plants of the treatments irrigated with the effluent presented statistically superior results those cultivated without irrigation in the characteristics: number of secondary cladodes, height of plants, length and perimeter of the cladodes. The chemical characteristics of the soil in the 0-20 cm layer after 234 days of fertirrigation with the effluent presented favorable conditions for the continued cultivation of the palm. The treatments submitted to the highest irrigation frequencies showed a slight tendency to acidification and a small increase in EC. The PST remained at the normal level for most treatments and only the 2.3 day fertirrigation presented solubic level. The levels of SB, CTC, V, K, Ca, Mg and P showed small variations among the treatments, with average, good and very good. Extraction / export of N, P, Na, Fe and Zn nutrients showed no significant difference between treatments, with significant difference in Ca / Mg, K, Cu and Mn extraction / export. The amounts of green and dry mass were higher in the fertigation treatments, increasing their values as the frequency of irrigation intensified. The treatment of domestic sewage by TEE was efficient, favoring the fertirrigation of the forage palm